Successful Foresight Study: Implications for Design, Preparatory Activities and Tools to Use - Dirk Meissner; Mario Cervantes (Foresight and STI Governance)
Foresight exercises have become common in many countries and regions. Although the concept of Foresight has been widely discussed within the academic community and among practitioners, it still remains rather unclear which activities are necessary before such a study is launched, and which instruments and tools are most suitable to meet the challenges of predicting the future. The article explores Foresight studies implemented on a national level in OECD and European Research Area (ERA) countries, in order to identify the necessary initial steps to be taken and tasks to be fulfilled prior launching Foresight projects.